Horrid Henry and the zombie vampire - Simon, Francesca (Sourcebooks Jabberwocky, 2012)
Henry knows that a class sleepover at a museum can only be one thing--boring! So he's invited a few party crashers to liven things up...zombie vampires! Plus three other stories that will leave you screaming for more.